A new species of Euchalcia Hübner, [1821] from Kazakhstan (Lepidoptera, Noctuidae) - Volynkin, Anton V.; Titov, Sergey V.; Ivanova, Maria S. (Zootaxa, 2014)
The Holarctic genus Euchalcia Hübner, [1821] belongs to the tribe Plusiini of the subfamily Plusiinae. The genus is one of the largest in the Plusiinae, comprising about 54 described species. The systematics of Eurasian and North African members of the genus was recently revised (Ronkay et al. 2008). In June 2013, in the course of faunistic studies on Noctuidae of the Tarbagatai Mts. (East Kazakhstan), a long series of an undescribed species of the genus was collected. Two additional specimens from the Dzhungarsky Alatau Mts. (South-East Kazakhstan) were found in the collection of the Siberian Zoological Museum (Novosibirsk). The species is described herein as new. It belongs to the E. inconspicua group within the E. inconspicua species-complex (Ronkay et al. 2008). The E. inconspicua group comprises two described species only: E. inconspicua (Graeser, 1892) and E. anthea L. Ronkay, G. Ronkay & Behounek, 2008. The new species is the northernmost member of the group. Institutional acronyms are as follows: AVB—coll. A.V. Volynkin, Barnaul, Russia; MČK—coll. M. Černila, Kamnik, Slovenia; NHMW—Naturhistorisches Museum, Vienna, Austria; STP—coll. S.V. Titov, Pavlodar, Kazakhstan; SZMN—Siberian Zoological Museum of the Institute of Animal Systematic and Ecology of the Siberian Branch of the Russian Academy of Sciences (Novosibirsk, Russia), ZISP—Zoological Institute of Russian Academy of Sciences, St. Petersburg, Russia.